Topological Equivalence of Morse–Smale Vector Fields with beh2 on Three-Dimensional Manifolds - Prishlyak, O. O. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
For the Morse–Smale vector fields with beh2 on three-dimensional manifolds, we construct complete topological invariants: diagram, minimal diagram, and recognizing graph. We prove a criterion for the topological equivalence of these vector fields.